Romanticism and the Christian Tradition of the Western Culture - Čiočytė, Dalia (Literatūra, 2015)
The article clarifies the notion of unity seen in the history of Western (Christian) culture; the notion is implied in investigations made by Rene Burke, Aidan Day, George Steiner. According to these scholars, the only cultural break that can be clearly seen in Western culture took place at the end of the 19th – beginning of the 20th centuries, when egocentric and nihilistic elements of the modern/postmodern conception of the world began to come into opposition with the Christian world-view. While considering the tension between traditional and “antitraditional” Western cultures, the article stresses the philosophical assumptions that undermine both cultures. The first signs of this cultural break can be seen in the period of Romanticism. Even though Romanticism is still strongly connected with the Western tradition, including its Christian aspect (the romanticists were strongly interested in the spiritual and the transcendental), the main aspects of Romanticism (egocentrism, homotheism, anticommunal tendencies) strongly oppose the tradition of Christian conception of the world. In the works of English, German, Polish, Russian Romanticists a double movement can be observed away from the traditional Christian philosophy and back towards it. Lithuanian Romanticism has hardly any such phenomena of double movement, it doesn’t quarrel with Christian thought. The article ends with the consideration of possible causes and consequences of this lack of opposition to the Christian world-view seen in Lithuanian Romanticism.